A New Surgical Technique for Ingrown Toenail. (13th May 2012) - Mousavi, Seyed Reza; Khoshnevice, Jaledin
Abstract : Background . Ingrowing toenails are a common condition which, when recurrent and painful, are often treated surgically. The aim of this study is to present a new simple surgical technique for ingrown toenails with good results. Method and Patients . The selected 250 patients with affected toes were surgically treated by our technique and observed from 1998 to 2004. Marginal nail elevation combined with surgical excision of the granulation tissue was more successful. For fixing the nail margin on the toe we have done one-bite suture by Nylon 3/0 that was removed after 3 weeks. Results . All patients were operated on by our new technique and the outcome was excellent; recurrence and failure of the technique were very low. Discussion . Because with this simple technique we excise the granulation tissue and elevate margin of nail over the skin, we will have higher cure rate, shorter postoperative pain, lower risk of postoperative infection, and remarkable cosmetic result without deformity; hence this technique should be considered as an alternative method of treatment.